An adolescent with idiopathic pleuroparenchymal fibroelastosis. Case report - KARADAĞ, BÜLENT TANER; ERDEM ERALP, ELA; KIYAN, GÜRSU; GÖKDEMİR, YASEMİN (SOC ARGENTINA PEDIATRIA, 2018)
Idiopathic pleuroparenchymal fibroelastosis (IPPFE) is a rare disorder recently included in rare idiopathic interstitial pneumonias according to the updated American Thoracic Society/European Respiratory Society classification. IPPFE is characterized by pleural and subpleural parenchymal fibrosis causing volume loss predominantly in the upper lung lobes. Age of onset is variable, IPPFE mainly occurs in third and fourth decades. We present a 16 year old patient with a 2-year history of exertional dyspnea, nonproductive cough and weight loss. On physical examination, auscultation revealed diminished breath sounds on the upper lobes. Chest radiograph showed apical pleural thickening and volume loss. Computerized tomographic scan (CT) of chest revealed ground glass densities and tubular bronchiectasis predominantly in upper lobes bilaterally, with interlobular septal thickening of the pleura and enlarged mediastinal lymph nodes. Thoracoscopic lung biopsy was performed and histological evaluation showed subpleural fibrosis and elastic staining demonstrated fragmented elastic fiber deposition in the subpleural area and adjacent pulmonary parenchyma suggesting IPPFE. To our knowledge this is the first case in childhood. Therefore, pediatricians should be aware of this disease for the diagnosis and appropriate management.
Keywords: child; intersititial lung disease; fibrosis; ENTITY